Representation of modernization of public consciousness in the mass media discourse - Dina Sabirova, Almagul Zadayeva, Valentina Zhumagulova, Gulzhan Kazhigaliyeva, Aigul Onalbayeva, (Opción, 2019)
This article deals with the axiological and linguo-cultural aspects of the linguistic representation of the modernization of public consciousness in the Russian-language in the discourse of the Kazakh media via linguoa-cognitive analysis. As a result, the lexeme people most often functions in the emotional-value context of unity and consolidation of the people. In conclusion, the potential for an influence of the modernization of public consciousness in the Kazakh Russian-language media is based on the construction of a single, interconnected, conceptual, axiological, linguistic, and ideological model consisting of the interrelated concepts